Science fiction cinema and 1950s britain : recontextualizing cultural anxiety (2018)
A nuclear test takes place in the Arctic Circle. The explosion melts the ice that has kept a gigantic, reptilian beast in a deep sleep since prehistoric times. Once awoken, the creature carves a path of destruction along North America’s Atlantic coast, ending in a deadly rampage through New York City. This sequence of events, which forms the plot of the American 1950s science fiction film The Beast from 20,000 Fathoms (1953), has tended to be interpreted in both academic and popular writing as a metaphorical representation of US Cold War anxieties about nuclear weaponry, with the monster serving as an embodiment of the dangerous potential of the explosion that released it.1 Drawing on the seminal work of Susan Sontag, a number of the era’s American radioactive monster movies have similarly been connected by scholars and critics to US fears of nuclear technology and particularly Soviet nuclear weaponry.2 However, these anxieties were not consistent across every nation to which these films were exported. Across the Atlantic Ocean, Britain was engaged in a period of what Keith Chapman has described as ‘considerable optimism’ about nuclear technology, culminating in the opening of ‘the first nuclear plant in the world to supply power on a commercial rather than an experimental basis’ in 1956.3 The promise of cheap electricity allowed the British nuclear industry to promote itself as ‘a tremendous opportunity for growth and prosperity in postwar economic development’.4 The financial opportunities presented by nuclear technology were framed by Britain’s significant debt to America as a result of the Anglo-American Loan Agreement of 1946 and the struggle to recover the nation’s former economic strength after the Second World War. While 1950s science fiction films have often been made sense of as representations of American Cold War nuclear anxieties, in Britain, where The Beast from 20,000 Fathoms was released in 1953, a different relationship to nuclear technology was emerging